2018
DOI: 10.7567/apex.11.061501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of nitrogen atoms in Al2O3gate dielectric of wide-bandgap-semiconductor MOSFET on gate leakage current and negative fixed charge

Abstract: We performed first-principle calculations to investigate the effect of incorporation of N atoms into Al2O3 gate dielectrics. Our calculations show that the defect levels generated by VO in Al2O3 are the origin of the stress-induced gate leakage current and that VOVAl complexes in Al2O3 cause negative fixed charge. We revealed that the incorporation of N atoms into Al2O3 eliminates the VO defect levels, reducing the stress-induced gate leakage current. Moreover, this suppresses the formation of negatively charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…First-principles calculations have revealed that charge traps in Al 2 O 3 originate from negatively charged complexes of oxygen and aluminum vacancies (V O V Al complexes) and that the trapping phenomenon is an inherent characteristic of Al 2 O 3 . 301) This means that Al 2 O 3 gate dielectrics require special considerations if they are to be applied to SiC power devices. Nitrogen incorporation (AlON) is a plausible way to alleviate the charge trapping phenomena.…”
Section: Challenges To Achieving An Ideal and Pure Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…First-principles calculations have revealed that charge traps in Al 2 O 3 originate from negatively charged complexes of oxygen and aluminum vacancies (V O V Al complexes) and that the trapping phenomenon is an inherent characteristic of Al 2 O 3 . 301) This means that Al 2 O 3 gate dielectrics require special considerations if they are to be applied to SiC power devices. Nitrogen incorporation (AlON) is a plausible way to alleviate the charge trapping phenomena.…”
Section: Challenges To Achieving An Ideal and Pure Interfacementioning
confidence: 99%
“…154,299,300) Moreover, firstprinciples calculations have revealed the mechanism by which V O V Al complex formation is suppressed under electrical stressing due to the nitrogen incorporation. 301) There is an ALD-based method of producing high-quality AlON films with suitable nitrogen concentrations ranging from 8% to 17%. 302) Obviously, AlON gate dielectric is also applicable to the nitride semiconductors; indeed, high-current and highvoltage (20 A-730 V) MOS-gated AlGaN/GaN heterojunction field-effect transistors (HFETs) have successfully been demonstrated.…”
Section: Challenges To Achieving An Ideal and Pure Interfacementioning
confidence: 99%
“…The nitrogen incorporated in the alumina of AlON film reduces the electrical defects in the insulator and improves the stability against charge injection. In Al 2 O 3 film, the defect levels of oxygen vacancies ( V o ) reportedly generate the leakage current, and complexes of V o and Al vacancies induce a negative fixed charge . Both the leakage current and negative fixed charge are reduced in AlON.…”
Section: Introductionmentioning
confidence: 99%
“…The negative charges can be related to the metal ion vacancy and, eg. Zr vacancy for ZrO 2 film, and Al vacancy for Al 2 O 3 film [29,30], and the negative charges are mobile [31][32][33]. The underlying mechanism for the P-V loops is the switching of dipoles formed by the V O 2+ and negative charges, which is a long range P switching during the electric field cycling [34].…”
Section: Methodsmentioning
confidence: 99%